Research outcome of sustainable solar drying technology dissemination for preserving perishable agriculture and horticulture crops in the North Western Himalayan region of India. (October 2022) - Aggarwal, R.K.; Singh Chandel, Shyam; Gorjian, Shiva; Chandel, Rahul
Highlights: Sustainable solar drying technology for perishable crops, is presented. Experimental results of marketable solar dried hill products are analysed. Quality parameters for value addition of solar dried products, are identified. Farmer feedback on solar dryers and drying techniques, are evaluated. Implementation strategy for solar drying techniques for farmers, is outlined. Abstract: Solar drying in a controlled environment offers one of the best options to preserve perishable crops. The objective of the present study is to work toward achieving UN sustainable Goal targets by 2030 through sustainable solar dryer designs and crop drying techniques based on years of experimentation and field implementation. In this study, low-cost free of maintenance innovative solar dryer designs, and research results of solar drying of commercial agricultural and horticultural crops grown in the North-Eastern Himalayan region of India, are presented. The farmer feedback survey results of field-installed solar dryers in different climatic zones of the region varying from low hills to high altitude snowbound regions are critically analysed. The quality parameters of the solar dried products namely color, reducing sugar, total sugar, and ascorbic acidity, are found to be commercially acceptable thus enhancing the market potential of the solar dried products. The newly developed low-cost indirect solar dryers with automation can easily be propagated worldwide. The market value of some solar-dried fruit products is found to enhance from 29% to 200% due to better quality, appearance, and taste, thus providing better returns to farmers and moving towards sustainable agriculture development.